On the Calviriidae Martens and Curini-Galletti, 1993 (Platyhelminthes, Proseriata), with the description of three new species - Schockaert, Ernest R.; Curini-Galletti, Marco; de Ridder, Wouter; Artois, Tom (Zootaxa, 2011)
Three new species of Calviriidae are described, belonging to two new genera: Diskeria gigantea n.g. n.sp., D. tasmanica n.sp. and Paracalviria islandica n.g. n.sp. The species of Diskeria have a copulatory organ with two rings of needles of which the internal ring forms a structure resembling a stylet. The accessory organ has a large glandular reservoir connected by a muscular duct to a “true” stylet surrounded by needles. The two species can be discerned by the number and size of the needles in the copulatory organ and in the accessory organ. In the female system there is a large terminal bursa. Paracalviria islandica has a copulatory organ with one circle of ±60 needles and an unarmed, sucker-like accessory organ in the male atrium. The female system is very simple without a bursa. Contrary to the other members of the Calviriidae, P. islandica has an epidermis with insunk nuclei, no septum in front of the pharynx and no sphincter around the gut above the pharynx. The relationships of and within the Calviriidae are discussed and compared with the recent results based on DNA analyses. Morphological arguments are given for the monophyly of the taxon Calviriidae. Amended diagnoses for the family and the four genera within the family are provided.